Guiding Growth: Early Interceptive Orthodontics in Mixed Dentition — A Clinical Case Series - Sulekha Doley; Joby Peter; Sonal Gupta; Rohan Shrivastava; Anindita Talukdar (UNIVERSITY JOURNAL OF DENTAL SCIENCES, 2026)
Background- Early orthodontic intervention is crucial for establishing functional and harmonious occlusion. Early interceptive modalities, particularly for crossbite, open bite, hypoplastic maxilla, developing class III malocclusion and oral habits, effectively restore normal occlusal relationships at the onset of malocclusion. Beyond tooth alignment, such treatments address skeletal discrepancies, improve oral function, and stabilise soft tissue posture to ensure long-term stability.Case Presentation- This case series reports three patients aged 8–9 years in the mixed dentition stage, presenting with anterior open bite, anterior and posterior crossbite, developing class III malocclusion, constricted maxilla, mouth breathing and tongue thrusting habits. Management involved myofunctional exercises, habit breaking appliance, ENT referral and maxillary expansion to correct dental and functional discrepancies.  It also includes protraction face mask therapy for correcting hypoplastic maxilla. At the 12‑month follow‑up, all cases demonstrated stable occlusal relationships consistent without relapse.Conclusion- The presented cases illustrate that interceptive treatment during mixed dentition supports skeletal and airway development, while habit correction and myofunctional therapy enhance long‑term stability. Early intervention reduces the complexity of later orthodontic needs, and interdisciplinary collaboration—particularly ENT referrals for mouth‑breathing children optimizing the outcomes. The timely management prevents malocclusion progression and promotes balanced craniofacial development, highlighting the broader significance of interceptive care in paediatric dentistry.